INTERNET ADDICTION, PSYCHOLOGICAL DISTRESS AND SLEEP DEPRIVATION AMONG UNIVERSITY STUDENTS - Abbas, Dr Saleem; Rafiq, Ayesha; Yasin, Kalsoom (PAKISTAN ISLAMICUS (An International Journal of Islamic & Social Sciences), 2023)
The main objective of the present study was to explain the relationship of internet addiction, sleep deprivation and psychological distress among university students. After a detailed literature review, it was hypothesised that 1). there is a remarkable association between internet addiction, sleep deprivation and psychological distress among university students. 2). Internet addiction predicts sleep deprivation and psychological distress among university students. For this study, 400 students, including 200 males and 200 females, were designated randomly from the diverse government and private universities. In order to measure the variables, the Internet addiction scale, sleep quality scale and Kessler psychological distress scale were used. Data was analysed through the SPSS-26 version by applying Pearson correlation and linear regression analysis. Findings of the current research have shown that there is a significant relationship between prevailing internet addiction, sleep deprivation and psychological distress in university students<.05 While it has also been approved that internet addiction is a strong predictor of sleep deprivation and psychological distress in university students (P<.05). At the end of the article, implementation and limitation of the current study, the recommendations for future studies, have been discussed in detail.